Mycorrhizal inoculation and fertilizer microdosing interactions in pearl millet (Pennisetum glaucum) under greenhouse conditions - Ndiaye, Malick; Mollier, Alain; Diouf, Adama; Diop, Tahir Abdoulaye (Frontiers in Fungal Biology, 2024)
Soil fertility is a major constraint to agricultural development in the Sahel region of Africa. One alternative to reducing the use of mineral fertilizers is to partially replace them with microbes that promote nutrition and growth, such as arbuscular mycorrhizal fungi (AMF). Mineral fertilizer microdosing is a technique developed to enhance fertilizer efficiency and encourage smallholder farmers to adopt higher mineral fertilizer application. A pot experiment was set up to study the effects of AMF inoculation on the mineral nutrition of pearl millet under mineral fertilizer microdosing conditions. The experimental set-up followed a randomized complete block design with five replicates. The treatments tested on millet were an absolute control and eight microdoses derived from the combination of three doses of 15-10-10 (NPK) mineral fertilizer (2 g, 3 g, and 5 g per pot), three doses of urea (U) (1 g, 2 g, and 3 g per pot), and three doses of organic manure (OM) (200 g, 400 g, and 600 g), combined with and without AMF (Rhizophagus irregularis and Rhizophagus aggregatum). The parameters studied were growth, root colonization by AMF, and mineral nutrition. Plant height, stem diameter, root dry biomass, and percentage of root mycorrhization were measured. The results revealed a significant effect of the fertilizers on the growth of pearl millet compared to the control. AMF and OM treatments resulted in the highest biomass production. AMF combined with microdoses of NPK improved N and Ca concentrations, while their combination with organic matter mainly improved the K concentration. Combining AMF with microdosed NPK and compost enhanced Zn and Ni concentrations. Root colonization varied from 0.55 to 56.4%. This investigation highlights the positive effects of AMF inoculation on nutrient uptake efficiency when combined with microdosing fertilization.